Wuhu decoction combined with azithromycin for treatment of Mycoplasma pneumoniae pneumonia in Asian children: a systematic review and meta analysis of randomized controlled trials - Yang, Shuo; Liu, Xinying; Wang, Huizhe; Wang, Haokai; Sun, Dan; Han, Yaowei; Li, Huanmin; Li, Xinmin (Frontiers in Pharmacology, 2024)
Objective: This study constitutes a pioneering systematic review and meta analysis delving into the clinical efficacy and safety of the combined therapy involving Wuhu Decoction and azithromycin for treating Mycoplasma pneumoniae pneumonia in pediatric patients. Methods: This study conducted a comprehensive computerized search to collect randomized controlled trials related to the combined use of Wuhu Decoction and azithromycin for treating Mycoplasma pneumoniae pneumonia in pediatric patients. The search was extended until August 2023. Two independent researchers were involved in literature screening, data extraction, and bias risk assessment. Meta-analysis was performed using Stata 14.0 and RevMan 5.4 software. Additionally, meta-regression analysis and subgroup analysis were carried out on primary outcomes to identify potential sources of heterogeneity and confounding factors. Results: A total of 22 randomized controlled trials involving 2026 patients were included in this study. The combined therapy of Wuhu Decoction and azithromycin demonstrated superior efficacy compared to azithromycin alone (RR = 1.17, 95% CI [1.13, 1.21], P < 0.00001; low certainty of evidence). Additionally, patients receiving the combination therapy experienced significantly reduced the disappearance time of fever (MD = -1.42, 95% CI [-1.84, -1.00], P < 0.00001; very low certainty of evidence), disappearance time of cough (MD = -2.08, 95% CI [-2.44, -1.71], P < 0.00001; very low certainty of evidence), disappearance of pulmonary rales (MD = -1.97, 95% CI [-2.31, -1.63], P < 0.00001; very low certainty of evidence), and disappearance time of wheezing (MD = -1.47, 95% CI [-1.72, -1.22], P < 0.00001; very low certainty of evidence). Meta-regression analysis suggested that course of disease, sample size, and age might be sources of heterogeneity. Subgroup and sensitivity analyses reaffirmed the stability of these results. Conclusion: Based on our meta-analysis findings, the combined therapy of Wuhu Decoction and azithromycin for treating pediatric Mycoplasma pneumoniae pneumonia exhibited superior overall efficacy in comparison to azithromycin monotherapy. However, in the included 22 studies, the majority of evaluated factors showed unclear bias risks, and a persistent bias risk was consistently present within one category. Moreover, due to the low quality of evidence, interpreting these results should be approached with caution.